Morphological and DNA sequence data uncover a new millipede species in the Thyropygus opinatus subgroup and assign T. peninsularis to this subgroup (Diplopoda: Spirostreptida: Harpagophoridae) - Piyatida Pimvichai; Henrik Enghoff; Karin Breugelmans; Brigitte Segers; Thierry Backeljau (PeerJ)
The millipede genus Thyropygus Pocock, 1894 is one of the most diverse genera within the family Harpagophoridae in Southeast Asia. The Thyropygus opinatus subgroup, belonging to the T. allevatus group, is distinguished by the presence of an additional projection on the anterior coxal fold. Here, we describe a new species of the T. opinatus subgroup, Thyropygus payamense sp. nov., from Payam Island, Ranong Province, Thailand, based on morphological and DNA sequence data. The mean interspecific COI divergence between the new species and other Thyropygus species is 0.13 ± 0.02 (range: 0.07–0.16). The new species is distinguished by (1) a small, slender, pointed spine at base of femoral spine, (2) a short, triangular mesal process of the anterior coxal fold, and (3) a short, slender, slightly mesad-curving tibial spine. Additionally, T. peninsularis Hoffman, 1982 is confirmed as a member of the T. opinatus subgroup, because it shares key gonopodal characters with other species in this subgroup, while COI and 16S rRNA sequence data firmly support this new classification, with a mean interspecific COI sequence divergence of 0.13 ± 0.03 (range: 0.07–0.17) from other species in the T. allevatus group. An identification key for all 29 species in the T. opinatus subgroup is provided. Further research is needed to assess the taxonomic status of, and phylogenetic relationships within, this subgroup, which, except for two species, may tentatively represent an endemic species radiation in the peninsular area of Thailand, Malaysia and Myanmar.